Training Nurses for Interdisciplinary Communication with Families in the Intensive Care Unit: An Intervention - Krimshtein, Nina S. (Mary Ann Liebert, Inc., 2011)
BACKGROUND: Critical care nurse communication training has largely been limited to didactic materials, interactive training for nurse supervisors, or brief participatory learning programs within the context of comprehensive end-of-life care educational seminars. Preliminary evidence suggests that an interactive approach can also be effective in communication skills training for intensive care unit (ICU) nurses. METHODS: We implemented a 1-day educational intervention in five acute care hospitals within Veterans Integrated Service Network (VISN) 3 (New York-New Jersey region) of the Department of Veterans Affairs and focused solely on communication skills and targeted specifically to nurses providing bedside care for critically ill patients. A “learner centered” approach to skills training that has several integral components was employed. Among these are: a cognitive, evidence-based foundation upon which to build new skills; a method such as role-play that allows participants to practice newly learned skills; and an affective component, during which trainees can freely discuss their impressions of the exercise or explore difficulties that may have been encountered. Before and after the program we conducted a detailed assessment of participants' self-rated communication skills and of the techniques and materials we used. RESULTS AND CONCLUSIONS: Post-program responses documented significant improvement in self-evaluated skills for each of the core tasks we assessed. Evidence suggests that communication with patients and families in the ICU can be most effectively approached in an interdisciplinary way. For nurses to fully realize their potential for optimal communication as members of the multidisciplinary team, they must be equipped with the necessary skills. We believe this new program helps to expand the range of approaches for training nurses in essential communication skills.